1994
DOI: 10.2307/1243753
|View full text |Cite
|
Sign up to set email alerts
|

Human Capital, Producer Education Programs, and the Adoption of Forward‐Pricing Methods

Abstract: Using a sample of 509 Kansas producers, we evaluate factors affecting adoption of forward pricing methods. We focus on producers' human capital accumulation and its effect on adoption of forward‐pricing techniques. Probit models are employed to evaluate producers' participation in educational programs and their forward‐pricing adoption decisions. Tobit models are employed to evaluate individual levels of adoption of these techniques in the marketing of wheat, corn, grain sorghum, soybeans, and cattle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
110
2
7

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(137 citation statements)
references
References 10 publications
18
110
2
7
Order By: Relevance
“…The negative sign of the coefficient of the yield risk premium variable is of interest since it implies that the more risk averse a producer is, the less likely he/she is to use forward pricing methods to manage price risk. The negative influence is consistent with the findings of Shapiro & Brorsen (1988); Goodwin & Schroeder (1994); Musser et al (1996);and Sartwelle et al (1999). Isengildina & Hudson (2001), however, found the relationship to be positive.…”
Section: Logistic Regression Of the Factors Which Affect The Adoptionsupporting
confidence: 91%
See 2 more Smart Citations
“…The negative sign of the coefficient of the yield risk premium variable is of interest since it implies that the more risk averse a producer is, the less likely he/she is to use forward pricing methods to manage price risk. The negative influence is consistent with the findings of Shapiro & Brorsen (1988); Goodwin & Schroeder (1994); Musser et al (1996);and Sartwelle et al (1999). Isengildina & Hudson (2001), however, found the relationship to be positive.…”
Section: Logistic Regression Of the Factors Which Affect The Adoptionsupporting
confidence: 91%
“…Goodwin & Schroeder (1994) argue that a more educated farmer is more likely to adopt a new technology and thus, to use forward pricing methods. The yield risk premium of the farmer is also expected to have a positive influence on the use of forward pricing methods since risk aversion becomes the primary motive for farmers to use forward markets (McNew & Musser, 2000).…”
Section: + Off-farm Economic Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with the notion that well-educated producers have the human capital to more fully comprehend and utilize the nuances of effectively utilizing risk management strategies (Goodwin and Schroeder, 1994;Smith and Baquet, 1996;Mishra and El-Osta, 2002;Ayinde, 2008;Margerita et al, 2009). …”
Section: Socio-economic Characteristics Of the Poultry Farmerssupporting
confidence: 62%
“…A total of 56 % of the respondents reported that they also had livestock in their farm operation. This group of farmers appears similar to commercial farmers described in previous surveys in terms of age (43 years in Shroeder et al, 1998) and farm size (1,732-1,450 acres in Patrick, et al, 1996; an average of 1,572 acres in Goodwin and Schroeder, 1994;and $473,850 average gross income in Coble, et al, 1999). The respondents to the survey were similar to participants of the Coble et al (1999) survey in terms of their usage of futures and options contracts, with about 30 percent of producers reporting the use of these forward pricing tools.…”
Section: Sample Characteristics and The Levels Of Mas Usesupporting
confidence: 84%